2024
DOI: 10.1021/acs.chemrev.3c00896
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Flexibility of Atomically Precise Metal Clusters

Si Li,
Na-Na Li,
Xi-Yan Dong
et al.

Abstract: Ligand-protected metal clusters possess hybrid properties that seamlessly combine an inorganic core with an organic ligand shell, imparting them exceptional chemical flexibility and unlocking remarkable application potential in diverse fields. Leveraging chemical flexibility to expand the library of available materials and stimulate the development of new functionalities is becoming an increasingly pressing requirement. This Review focuses on the origin of chemical flexibility from the structural analysis, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 684 publications
(1,731 reference statements)
0
2
0
Order By: Relevance
“…Atomically precise metal clusters are a class of molecules that are well-known for their diverse properties. Their structural integrity, composition, and electronic confinement make them promising candidates for various applications. Over the past decade, exploring the reactions between atomically precise metal clusters has evolved as a new research area of interest. These reactions in the solution phase and in the gas phase have been probed using mass spectrometry. In such reactions, the exchange of metal atoms and ligands occurs, while maintaining the nuclearity of individual clusters. Neumaier et al have reported the kinetics of the reaction between the clusters [Au 25 (PET) 18 ] − and [Ag 25 (DMBT) 18 ] − in the solution .…”
Section: Introductionmentioning
confidence: 99%
“…Atomically precise metal clusters are a class of molecules that are well-known for their diverse properties. Their structural integrity, composition, and electronic confinement make them promising candidates for various applications. Over the past decade, exploring the reactions between atomically precise metal clusters has evolved as a new research area of interest. These reactions in the solution phase and in the gas phase have been probed using mass spectrometry. In such reactions, the exchange of metal atoms and ligands occurs, while maintaining the nuclearity of individual clusters. Neumaier et al have reported the kinetics of the reaction between the clusters [Au 25 (PET) 18 ] − and [Ag 25 (DMBT) 18 ] − in the solution .…”
Section: Introductionmentioning
confidence: 99%
“…Thiolate-protected gold nanoclusters (TP-AuNCs) have sparked immense interest for their distinctive quantum size phenomena, remarkable physicochemical attributes, and high potential for applications in fields like optics and biomedicine. The remarkable progress in TP-AuNCs has ignited fervent interest among experimental scientists in crystalline structure preparation. Specifically, since Kornberg et al successfully resolved the first crystal structure of the TP-AuNC Au 102 (SR) 44 (SR = thiolate ligand), numerous other structures of TP-AuNCs have been crystallized. , The successful characterization of these crystalline structures reveals that TP-AuNCs of various sizes and morphologies consist of internal gold cores, external “staple” motifs SR[Au(SR)] x (x = 0, 1, 2, 3, ...), and overall charge states. , …”
Section: Introductionmentioning
confidence: 99%